Biochemical and haematological responses to starvation in an air breathing fresh water teleost Heteropneustes fossilis (Bloch) - Borah, Sabita; Yadav, R N S (Indian Journal of Fisheries, 2011)
Lactate dehydrogenase (LDH) activity, amount of protein glucose, glycogen and some haematological parameters of Heteropneustes fossilis (Bloch) were investigated during starvation upto 30 days. The activity of lactate dehydrogenase showed significant decrease as the duration of starvation increased in both liver and muscles. The amount of protein, glucose and glycogen in the liver and muscle tissues also decreased as the period of starvation increased. In contrast the haemoglobin content and total RBC number increased during initial period of starvation and thereafter decreased significantly during later period of starvation.